FENOMENA MELEK POLITIK (Political Literacy) MASYARAKAT KOTA AMUNTAI KABUPATEN HULU SUNGAI UTARA - Akhmad Riduan; Budi Lesmana; Nasripani Nasripani; reno affrian (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2018)
The general election is actually the entry point for the improvement of public welfare in various aspects, whether political, economic, social, cultural and so on. In order to make an impact elections positively correlated with the welfare of the public, in addition to the background of the prospective participants/contestants election also required the political understanding of the citizens as voters because of political literacy is one factor that plays a major role in the quality of elections in a country.In Amuntai City, Hulu Sungai Utara district, political knowledge citizens are generally relatively low where political terms not understood as it should be in addition to confusion relevance between elections and regional development. Political participation of citizens in general is still low, especially those who work in the informal sector and tend to avoid involvement in practical political activity. Although they participated in the elections, but they just do not care about the output of the election itself. Furthermore, the political interest of citizens were generally quite low because most of them assess prejudice against political activity although no doubt some of those who assess positively to the political world.To increase the political understanding of citizens in Amuntai City, suggested to the election organizers in Hulu Sungai Utara district, especially the Election Commission and the Election Supervisory Committee to conduct an intense political socialization to the community, especially in rural areas. Political socialization should be cooperating with the participation of local governments, organizations of society and universities in the area. Political parties in the region should also undertake political socialization as the embodiment of one of the functions of political parties, especially in the areas that became the basis of a mass political party concerned with promoting political ethics that typically become one of the political ideology of political parties.